Generation of a conditional lima1a allele in zebrafish using the FLEx switch technology. Issue 1 (6th December 2015) - Jungke, Peggy; Hans, Stefan; Gupta, Mansi; Machate, Anja; Zöller, Daniela; Brand, Michael
Summary: Gene trapping has emerged as a valuable tool to create conditional alleles in various model organisms. Here we report the FLEx‐based gene trap vector SAGFLEx that allows the generation of conditional mutations in zebrafish by gene‐trap mutagenesis. The SAGFLEx gene‐trap cassette comprises the rabbit β‐globin splice acceptor and the coding sequence of GFP, flanked by pairs of inversely oriented heterotypic target sites for the site‐specific recombinases Cre and Flp. Insertion of the gene‐trap cassette into endogenous genes can result in conditional mutations that are stably inverted by Cre and Flp, respectively. To test the functionality of this system we performed a pilot screen and analyzed the insertion of the gene‐trap cassette into the lima1a gene locus. In this lima1a allele, GFP expression faithfully recapitulated the endogenous lima1a expression and resulted in a complete knockout of the gene in homozygosity. Application of either Cre or Flp was able to mediate the stable inversion of the gene trap cassette and showed the ability to conditionally rescue or reintroduce the gene inactivation. Combined with pharmacologically inducible site specific recombinases the SAGFLEx vector insertions will enable precise conditional knockout studies in a spatial‐ and temporal‐controlled manner. genesis 54:19–28, 2016. © 2015 Wiley Periodicals, Inc.